Oral Communication Skills of the Students of Osias Colleges, Inc. - Salagan, Aurea C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The study employed a descriptive design to gather baseline data on respondents' oral communication skills in English. The results revealed that the majority of respondents were female, aged 19-24, who primarily spoke Tagalog and Ilokano at home, and were mainly in their second and third years of study. Utilizing a 5-point Likert scale for assessment, the findings indicated that respondents were rated as "good" across various dimensions of oral communication, including audience engagement, context, transactional and interper-sonal skills, medium of exchange, and paralinguistics. This overall rating suggests that while their skills are adequate, there is consid-erable potential for improvement to enhance their competitiveness in the job market.As a result, the study underscored the need for a program aimed at strengthening students' oral communication skills in English, with an intervention proposed for review and implementation in the upcoming academic year. Recommendations for program heads and school administrators included incorporating these findings into curriculum evaluations and policy development. Regular curriculum mapping is essential to ensure that course objectives align with the enhancement of students' English oral communication skills. Addi-tionally, it is recommended that training programs focused on im-proving these skills be made available, and that language teachers engage in professional development seminars to refine their in-structional techniques. Furthermore, increasing the number of in-teractive classroom activities is advised to further cultivate stu-dents' oral communication abilities in English.